PEMANFAATAN KOMODITI LOKAL DALAM PENDAMPINGAN WIRAUSAHA MELALUI PELATIHAN DEVIL PANCAKE DI SMK NEGERI 2 SINGARAJA - Dia Aprilla Dua; Luh Eka Susanti; Anak Agung Ayu Arun Suwi Arianty (Fakultas Teknik dan Informatika Universitas PGRI Mahadewa Indonesia, 2024)
In the era of globalization and intense market competition, entrepreneurship is crucial for improving economic quality. One accessible form of entrepreneurship is through micro, small, and medium enterprises (MSMEs). Entrepreneurship allows communities to enhance their welfare and economic potential, regardless of age, offering vocational high school students the chance to become young entrepreneurs. Entrepreneurial mentoring for vocational high school students prepares them to innovate and develop strong entrepreneurial traits. This program, conducted in Buleleng Regency, Bali, known for its educational heritage, focuses on culinary entrepreneurship training, particularly in pastry making. Initiated by the Student Association of the D3 Hospitality Program at the International Tourism and Business Institute, the training includes practical food production using local commodities. One notable training involves making Devil Pancake, a simple yet innovative pastry. Participated by Culinary students from SMKN 2 Singaraja, using demonstration and duplication methods to enhance practical skills. Students observed instructors and then practiced independently, significantly improving their understanding and skills. The program yielded positive results, boosting students' confidence and practical experience. Using local ingredients and simple processes reassured students that starting a business is feasible. This program successfully motivated SMKN 2 Singaraja students to pursue entrepreneurship.